Exploratory mixed methods study of respiratory physiotherapy for patients with lower respiratory tract infections - Oliveira, Ana (2016)
Objectives To assess the outcomes of respiratory physiotherapy for patients with lower respiratory tract infections (LRTI). Design Parallel group mixed-methods study. Setting Patients were recruited from a general hospital. Respiratory physiotherapy took place in a community setting. Participants Fifty-four patients aged ≥18 years and diagnosed with LRTI completed the study. Twenty-seven patients were allocated to the control group {CG: 10 male, mean age 53.3 [standard deviation (SD) 17.4] years} and 27 patients were allocated to the experimental group [EG: 10 male, mean age 58.6 (SD 17.2) years]. Intervention The CG received conventional medical treatment and the EG received conventional medical treatment plus respiratory physiotherapy for 3 weeks. Outcome measures Patients in both groups undertook the 6-minute walk test (6MWT), modified Borg scale (MBS), modified Medical Research Council questionnaire (mMRC), and Breathlessness, Cough and Sputum scale (BCSS) before and after the intervention. A telephone follow-up survey was performed 3 months after the first hospital visit. Interviews were conducted immediately after the intervention in the EG. Results In the EG, the distance walked in the 6MWT increased by more than the minimally important difference (P = 0.001), and significantly more than the CG {EG: mean change 76 m [standard deviation (SD) 63], 95% confidence interval (CI) 51 to 101; CG: mean change 27 m (SD 56), 95% CI 5 to 49; mean difference between groups: 49 m 95% CI 16 to 82; partial η2 = 0.15}. No differences in the MBS, mMRC and BCSS were found between the two groups. The EG reported high levels of satisfaction with the intervention (27/27; 100%) and with the physiotherapist (20/27; 74%). The intervention improved patients’ symptoms (19/27; 70%) and their self-management skills to control/prevent future LRTI (19/27; 70%). Health service use was significantly less in the EG (P = 0.04). Conclusions Respiratory physiotherapy appears to be effective for the management of patients with LRTI